PENANAMAN KARAKTER PEDULI LINGKUNGAN MELALUI PELATIHAN PEMANFAATAN SAMPAH PLASTIK BAGI SANTRI AL MUHAJIRIN 1 JOMBANG - Yuliana, Anggi Indah; Chusna, Miftachul; Aziz, Andreas Abdul (JMM - Jurnal Masyarakat Merdeka, 2021)
Islamic boarding schools are a source of plastic waste in Jombang Regency. Efforts to reduce waste generation through reusing plastic waste must be supported by adequate skills from the Islamic boarding school community. This community service activity aimed to improve the knowledge and skills of students in managing plastic waste into pots as a medium for cultivating vegetables in narrow land. This activity was carried out in October 2020 at ma'had al Muhajirin 1 Pondok Pesantren Bahrul Ulum Tambakberas Jombang, the partiparticipant was about 15 students. The method used socialization and practiced activities. The evaluation of the results of the training showed that 70% of the training participants had good skills when making plastic waste pots, while 30% of the training participants were in the category with fairly good skills. These results indicated that this community service activity could improve the skills of students in processing plastic waste onto pots that were useful for planting vegetables.